Biodiesel production by immobilized lipase - Neo, Hui Pin (2010)
In order to preserve the global environment and ensure the long term supply of energy sources, there is a need to search for alternative energy sources. Among all the different renewable sources, biodiesel is considered as a potential substituent for conventional diesel fuels and extensive research has been focused on the production of biodiesel. Production of biodiesel through esterification reaction of Free Fatty Acid (FFA) catalyzed by immobilized Pseudomonas cepacia lipase (PCL) on modified zirconium oxide support was investigated. The focus of the project was on optimization of several process parameters, including choices of alcohol, molar ratio of ethanol to FFA, water content and enzyme loading. Ethanol was found to be more suitable as the reactant due to its environmental advantages. The oleic acid to ethanol molar ratio of 1:20 to 1:40, immobilized PCL loading of 90 mg to 300 mg and water content of 0 % vol/vol to 10 % vol/vol were studied. The highest conversion for each study can be achieved by using oleic acid to ethanol molar ratio of 1:30, 180 mg immobilized PCL and 0 % vol/vol of water content. The best result indicated that the activity of immobilized PCL was stable for at least seven consecutive runs and maintained in the range of 80.51% to 88.75% in the presence of co-solvent mixture with 20% tert-butanol and 80% isooctane by employing immobilized PCL on zirconia support modified with stearic acid. Future works may include investigating the solvent engineering method, exploring the combined used of system.